Pharmacological and Antagonistic Potentials of Mikania micrantha - Baral, Bikash; Bhattarai, Nabin; Vaidya, Geeta Shrestha (Nepal Journal of Science and Technology, 2012)
The antimicrobial, chemical and allelopathical properties of invasive alien weed Mikania micrantha Kunth ex H.B.K were analyzed. The extraction was performed in different solvents by soxhlet extraction technique. Some bacteria (Acinetobacter sp. and Bacillus subtilis) were found to be highly inhibited, whereas the extract was found effective against Fusarium species (F. eridiforme) among the fungi. Of all the solvents used for extraction, methanolic hot extract showed good antimicrobial properties against tested pathogenic strains. The preliminary qualitative phytochemical assay divulged the presence of glycosides and quinones in the test plant. Germination rate was higher for all crops with control treatment. The germination rate decreased with the increase in the extract concentration and was found to be lowest at 5% concentration of extract. Generally, the radicle length of all bioassayed species decreased with increasing concentrations of Mikania, with Barley and Paddy being the most susceptible to the plant extract at full strength. The broad spectrum of activity of the extract indicated possibilities for wide use of M. micrantha for controlling the human pathogenic bacteria and phytopathogenic fungus that have been widely destroying crops. DOI: http://dx.doi.org/10.3126/njst.v12i0.6483 Nepal Journal of Science and Technology 12 (2011) 75-84